Identities, Nations and Ethnicities: A Critical Comparative Study from Southeast Asia - T. King, Victor (International Journal of Humanities and Social Science Research, 2017)
The paper focuses on images of identity in Southeast Asia and argues that it is analytically useful to distinguish these identities and their “modes of representation” at different levels or scales of magnitude. In this regard, it is necessary to examine images of nationhood or the identities expressed and displayed at the national level in interaction with identities at the sub-national level which comprise what are usually referred to as ethnic groups or alternatively “peoples” or “communities”. Identity and its specific expression in “ethnicity” comprises a form of social cleavage and is a means of organizing social and cultural relations and encounters in terms of similarity and difference. It is argued that identity cannot exist apart from the establishment and maintenance of “cultural difference” and the construction and operation of boundaries, and is generated and sustained in relationships, both at the level of ideas and in practice with others who are perceived to be and categorized as “not us” or “other”. In other words, the ways in which identity and ethnicity in particular operate are “relational”. Comparative case-studies are taken from Singapore, Malaysia and Thailand to illustrate these propositions.